2021
DOI: 10.1097/bot.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Versus 2-Stage Bilateral Intramedullary Nail Fixation in Patients With Bilateral Femur Fractures: A Multicenter Retrospective Review

Abstract: Objective: To evaluate rates of complications in patients with bilateral femur fractures treated with intramedullary nailing (IMN) during either 1 single procedure or 2 separate procedures.Design: A multicenter retrospective review of patients sustaining bilateral femur fractures, treated with IMN in single or 2-stage procedure, from 1998 to 2018 was performed at 10 Level-1 trauma centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Comparing by fracture type addressed, Ristevski et al [1] reported a mean LOS of 39.7, 31.4, and 15.6 days for the prophylaxis, fracture, and combination subgroups undergoing SS bilateral femoral nailing procedures, respectively, although no comparison to a TS cohort was made. Similar results have also been shown in the trauma literature by Flagstad et al [48] who compared SS vs. TS bilateral femoral IMN and noted a significantly shorter LOS for SS versus TS cases (16.4 vs. 28.5 days; p < 0.01). Length of stay depends substantially on attaining pain control and functional independence and the SS approach may help expedite reaching this goal due to earlier stabilization of the weight-bearing bones and resumption of weight-bearing status [3,7].…”
Section: Blood Loss and Transfusionsupporting
confidence: 88%
See 1 more Smart Citation
“…Comparing by fracture type addressed, Ristevski et al [1] reported a mean LOS of 39.7, 31.4, and 15.6 days for the prophylaxis, fracture, and combination subgroups undergoing SS bilateral femoral nailing procedures, respectively, although no comparison to a TS cohort was made. Similar results have also been shown in the trauma literature by Flagstad et al [48] who compared SS vs. TS bilateral femoral IMN and noted a significantly shorter LOS for SS versus TS cases (16.4 vs. 28.5 days; p < 0.01). Length of stay depends substantially on attaining pain control and functional independence and the SS approach may help expedite reaching this goal due to earlier stabilization of the weight-bearing bones and resumption of weight-bearing status [3,7].…”
Section: Blood Loss and Transfusionsupporting
confidence: 88%
“…However, determination of optimal timing between the two surgeries is not clear as it depends on multiple factors and is difficult to decipher from existing studies due to limited, unclear, and heterogeneous data. Moreover, the selection of patients for SS vs. TS seems biased [22,31,48] and may influence the timing. Thus, it should be tailored to each patient's unique clinical situation and needs.…”
Section: Surgical Technique and Implant Considerationsmentioning
confidence: 99%
“…Interlocking nails are considered by many to be the standard of care for stabilization of critical-sized bone defects (Rhorer, 2009;Dejardin et al, 2012;Shen et al, 2016;Flagstad et al, 2021;Kang et al, 2021;Viberg et al, 2021). Intramedullary fixation is commonly used for both rodent and large animal critical gap healing models (Lindsey et al, 2006;Schoen et al, 2008;Rhorer, 2009;MSc et al, 2013;Quirk et al, 2016;Shiels et al, 2018;Ozmeric et al, 2020).…”
Section: Introductionmentioning
confidence: 99%